PROGRAM GERAKAN LITERASI SEKOLAH DALAM MENUMBUHKAN MINAT BACA SISWA KELAS IV - Wahab Cahya Saputra; Hera Heru Sri Suryanti; Elinda Rizkasari (Widya Wacana: Jurnal Ilmiah, 2023)
The purpose of this study was to describe the school literacy movement program in fostering interest in reading in class IV SD Negeri 1 Sambi Boyolali for the 2022/2023 academic year. This research method is descriptive qualitative. The subjects used in this study were fourth grade students, homeroom teachers and school principals. Sources of data obtained in the form of primary data and secondary data. Data collection techniques by observing, interviewing and documentation. The data validation technique was carried out by source triangulation and technique triangulation. Data analysis was carried out by: data collection, data reduction, data presentation, and data verification. Based on the results of the research, it can be concluded that, (1) the school literacy movement program in fostering interest in reading in class IV students of SD Negeri 1 Sambi has been going well in accordance with the GLS theory guidelines. (2) the obstacle to the school literacy movement program in fostering interest in reading in grade IV students is that there are students who sometimes do not want to take the initiative to read for 15 minutes if they are not supervised by the class teacher. (3) The teacher's efforts in carrying out the school literacy movement program by always campaigning for the GLS program at every moment such as the flag ceremony, before class starts and through the student's guardian WhatsApp grub.he letters "p, q, and x", and e) difficulty reading syllables 2) difficulty when learning to write, namely: a) writing is not neat, b) not being careful when writing, c) difficulty writing when leaving a distance between one letter and another, d) there are scribbles in the writing, e) difficulty when writing example sentences and words from the blackboard, f) difficulty when copying example words and sentences from the blackboard, g) difficulty when imitating examples of words and sentences from the blackboard, h) difficulty when drawing circles, and i) difficulty when drawing circle shapes and 3) factors that influence students' reading and writing abilities, namely: 1) internal factors, namely: a ) interest and b) motivation and 2) external factors, namely: a) family environment and b) school environment. Keywords: Program, School Literacy Movement, Interes in Reading